Environmental factors associated with the cover of Agave angustifolia (Asparagaceae) in the coastal scrubland of Yucatán, Mexico - Cervera Herrera, José Carlos; Leirana-Alcocer, Jorge Leandro; Navarro Alberto, Jorge A. (Instituto de Ecología, A.C., 2018)
Background and Aims: Agave angustifolia, or chelem, is the only wild species of the Yucatán Peninsula and is the ancestor of cultivated species with great economic and cultural values. It provides important environmental services such as food source for fauna, it fixes sandy soils and sequesters carbon in arid habitats with poor soils. It is a potential crop that may face the dryness exacerbation expected for the region and the genetic erosion of henequen. The aim of this work is to gather data about its population density, spatial pattern, size structure, and the relationship between its abundance and environmental factors of the Yucatán coastal scrublands, in order to assess the use of the species for ecological restauration purposes.Methods: Field work was carried out in three coastal sites: Chuburná (Ch), San Benito, (SB) and Río Lagartos (RL). Thirty six 4 m2 plots were placed in SB and RL; we estimated the relative cover of Agave angustifolia, shrubs higher than 1 m and litter in each plot. Potential of Hidrogen (pH), electric conductivity, total nitrogen, organic matter and bright index were measured from the soil samples collected. Population density, spatial pattern and size structure of A. angustifolia in SB and Ch were also described.Key results: The cover of Agave angustifolia is negatively correlated to the shrubs and litter cover, as well as the amount of organic matter. The population density was lower than 0.1 individuals/m2, small individuals dominated the population structure and the spatial pattern is aggregated.Conclusions: Because its ability to live in poor soils, high temperatures and solar radiation, the species could be used to restore some ecological functions in the most arid habitats of the coast where the vegetation has been severily damaged.